Application of physiotherapy in persons at risk of metabolic syndrome development - Zeman, Marek; Valaskova, Lenka (Neuro-endocrinology letters, 2017)
Problems the locomotor activity and nutritional provisions in the treatment of obesity or metabolic syndrome are currently widely discussed. Based on prevailing experience, the attention in the field of locomotor and fitness activities is rather general, i.e. is mainly focused on the development of the general body fitness and reduction fitness programmes. However, no long-term effects of the locomotor therapy can be expected without appropriate and particularly targeted physiotherapy with a thorough kinesiological examination. Case report described here monitored the course of a three-month physiotherapeutic intervention in person having enhanced values of the waist circumference in accordance with criteria of the metabolic syndrome, who previously attended a programme of diet provisions without meeting with success. In this case, positive results of reductions in the waist circumference and further dimensions were achieved in spite of the fact that in the course of the physiotherapy no arrangements of nutritional habits have been introduced.
Keywords: dospělí; Waist Circumference; Humans; Metabolic Syndrome; lidé; Female; Physical Therapy Modalities; techniky fyzikální terapie; Treatment Outcome; Adult; metabolický syndrom; výsledek terapie; ženské pohlaví; obvod pasu